2020
DOI: 10.1021/acsnano.9b04571
|View full text |Cite
|
Sign up to set email alerts
|

Tuning Ligand Density To Optimize Pharmacokinetics of Targeted Nanoparticles for Dual Protection against Tumor-Induced Bone Destruction

Abstract: Supporting InformationThe Supporting Information is available free of charge at https://pubs.acs.org/doi/10.1021/acsnano.9b04571. Further polymer characterization, in vitro BTNP behavior, pharmacokinetic parameters and mouse model results (PDF)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(27 citation statements)
references
References 101 publications
0
27
0
Order By: Relevance
“…According to the location of the tumor cells, we could divide the strategies into primary cancer targeting drug delivery and cancer metastasis-targeting drug delivery ( Fig. 1 and Table 1 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 ).
Figure 1 Targeting drug delivery strategies for tumor metastasis treatment.
…”
Section: Cancer Targeting Drug Deliverymentioning
confidence: 99%
See 1 more Smart Citation
“…According to the location of the tumor cells, we could divide the strategies into primary cancer targeting drug delivery and cancer metastasis-targeting drug delivery ( Fig. 1 and Table 1 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 ).
Figure 1 Targeting drug delivery strategies for tumor metastasis treatment.
…”
Section: Cancer Targeting Drug Deliverymentioning
confidence: 99%
“… 29 Dual-targeting tumor and other cells in metastasis Folic acid and alendronate-modified PLGA nanoparticles could dual-target bone mass and tumor cells in bone metastasis. 30 Modulating pre-metastasis niche S100A4 siRNA-loaded exosome could downregulate the expression of S100A4 in lung fibroblast, which significantly reduce breast cancer lung metastasis. 31 Hijacking circulating cells Hijacking platelet P-Selectin-modified redox-responsive paclitaxel-loaded micelle (PSN-PEG-SS-PTX4) could bind with activated platelet in circulation and then target to lung metastasis.…”
Section: Cancer Targeting Drug Deliverymentioning
confidence: 99%
“…One possible mechanism may include phagocytic cell uptake as described in the “ELVIS” effect (extravasation via leaky vasculature followed by inflammatory cell sequestration) 43,44 . Nevertheless, modifications to the nanoparticle chemistry have shown enhanced retention at target sites and allow for further improvement of nanoparticle accumulation in bone in other disease models 29 . Considering that sites of inflammation and infection are known to produce ROS 45 and that release of compounds from PPS nanoparticles is responsive to ROS concentration, it is likely that ROS levels at infected sites contribute to drug cargo release within bone.…”
Section: Discussionmentioning
confidence: 99%
“…DMA was purified by distillation under reduced pressure before polymerization. PPS (10 kDa), poly(propylene sulfide)‐4‐cyano‐4‐(ethylsulfanylthiocarbonyl)sulfanylpentanoic acid (PPS 135 ‐ECT), and poly(benzoyloxypropyl methacrylamide) (pHPMA‐Bz) were synthesized as described previously 29 …”
Section: Methodsmentioning
confidence: 99%
“…In contrast, GANT58 reduced expression of ITGB3 , GLI2 , and PTHRP in tumor cells cultured on both 2D films and bone-like 3D scaffolds, which highlights the potential of Gli2 inhibitors for blocking TIBD. It was recently shown that targeting Gli2 inhibition to the tumor-bone microenvironment effectively reduced TIBD in a model of breast cancer metastasis to bone [ 57 , 58 ]. Thus, this study emphasizes the importance of studying tumor cell signaling and response to therapeutics in 3D cultures that accurately capture the physical properties of the bone microenvironment.…”
Section: Discussionmentioning
confidence: 99%